2020
DOI: 10.21203/rs.3.rs-115378/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 Among Patients With Inflammatory Rheumatic Diseases

Abstract: Background: There are few data on disease characteristics and outcome of coronavirus 2019 (COVID-19) among patients with inflammatory rheumatic diseases (IRDs). In this cohort study, we aimed to report the disease characteristics and variables associated with COVID-19 outcome among patients with IRDs.Methods: Between April and June, 2020, 167 adult IRD patients with COVID-19 were registered from 31 centers in 14 cities in Turkey. Disease outcome was classified in 4 categories; (i) outpatient management, (ii) h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…Recent studies supported that patients who take biological and conventional DMARDs have less morbidity in the case of COVID-19 [2]. Moreover, in another study from Turkey consisting of 167 patients with inflammatory rheumatic disease, biologic and conventional DMARDs did not seem to cause worse outcomes [12]. However, overall, 18% of all the inflammatory arthritis patients discontinued bDMARDs in the first 100 days of the pandemic.…”
Section: Discussionmentioning
confidence: 94%
“…Recent studies supported that patients who take biological and conventional DMARDs have less morbidity in the case of COVID-19 [2]. Moreover, in another study from Turkey consisting of 167 patients with inflammatory rheumatic disease, biologic and conventional DMARDs did not seem to cause worse outcomes [12]. However, overall, 18% of all the inflammatory arthritis patients discontinued bDMARDs in the first 100 days of the pandemic.…”
Section: Discussionmentioning
confidence: 94%
“…Currently data confirming that COVID-19 severity in patients with IMIDs depends on well-known risk factors also described in the general population, including male sex, older age, and the presence of comorbidities, such as diabetes, obesity, renal, and pulmonary diseases. 7,10,11,28,30 During the pandemic, treatment with IM/IS in high-risk patients has been challenging to determine the best standard of care for SAR-CoV-2 infection. In general, IM/ IS seem not to affect COVID-19 course 7,30 ; however, if analyzed individually, some of them could have a beneficial effect, whereas others may be associated with ICU admission and death.…”
Section: Discussionmentioning
confidence: 99%
“…7,10,11,28,30 During the pandemic, treatment with IM/IS in high-risk patients has been challenging to determine the best standard of care for SAR-CoV-2 infection. In general, IM/ IS seem not to affect COVID-19 course 7,30 ; however, if analyzed individually, some of them could have a beneficial effect, whereas others may be associated with ICU admission and death. 10,11,28 Given the observational design of this registry, it has some important limitations.…”
Section: Discussionmentioning
confidence: 99%
“…In a cross-sectional study of 206 patients, 1 out of 77 patients on rituximab tested positive for COVID-19 immediately post-rituximab administration and had an uneventful course despite being elderly [15]. A recent multicenter study from Turkey concluded that biological treatment, including rituximab, does not seem to affect COVID-19 outcomes [16].…”
Section: Discussionmentioning
confidence: 99%